Phytochemical, Aphrodisiac and Anti-Hypertensive Properties of Pausinystalia Yohimbe - Okolo R. U (International Journal of Allied Medical Sciences and Clinical Research, 2020)
In order to investigate the folkloric and traditional use of Pausinystalia yohimbe (PY) in vivo experiments were conducted. Male rats weighing between 170 and 260gm were randomly chosen for the experiment for the in vivo study. Rats were lightly anesthetized with 20mg/kg im of ketamine and 30mg/kg of phenobarbitone intra peritonially. The anaesthesia was maintained with ketamine intravenously. The rats breathed spontaneously. The left femoral artery was catheterized using a PP50 polyethylene catheter and connected to a strain-gauge blood pressure transducer (connected to a Grass polygraph, model 7D) for BP measurement. A second catheter in the right femoral vein (PP50) was used for the injection of drugs or extract. A 24G needle placed in the corpus carvanosum tissue and connected to a strain-gauge pressure transducer was used to measure the intra-cavernous pressure. Normal saline was slowly injected through the femoral vein and recordings made for a period of 30 to 45 mins to serve as control. Eight rats were used for each set or group. The result from the in vivo study was a significant increase intra-cavernous pressure (ICP) indicating erectile potential of the PY crude extract. The mean arterial blood pressure was lowered significantly to below 80mmHg which latter rouse to 90mmHg for the PY treated group while that of the control remained above 110 mmHg throughout the experiment. Since PY extract could lower blood pressure and also enhance erectile functions it is likely to become novel drug in management of hypertensive patients with erectile dysfunction.